Optical system for camera flip chip application - Ng, Keh Chyun. (2008)
Design an imaging system based on thermoset material and study the tolerance sensitivity of the imaging system. The potential basic configuration of the lens system is found. The optical properties of a new thermoset material developed by the collaborator is measured and analyzed.